2016
DOI: 10.1016/j.neuint.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Mild mitochondrial metabolic deficits by α-ketoglutarate dehydrogenase inhibition cause prominent changes in intracellular autophagic signaling: Potential role in the pathobiology of Alzheimer's disease

Abstract: Brain activities of the mitochondrial enzyme α-ketoglutarate dehydrogenase complex (KGDHC) are reduced in Alzheimer’s disease and other age-related neurodegenerative disorders. The goal of the present study was to test the consequences of mild impairment of KGDHC on the structure, protein signaling and dynamics (mitophagy, fusion, fission, biogenesis) of the mitochondria. Inhibition of KGDHC reduced its in situ activity by 23–53% in human neuroblastoma SH-SY5Y cells, but neither altered the mitochondrial membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 64 publications
(89 reference statements)
2
28
0
Order By: Relevance
“…Mitochondria were isolated as previously described [41] with minor modifications. All steps were performed at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondria were isolated as previously described [41] with minor modifications. All steps were performed at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Neurons were pretreated with CESP (100 lM) and or t-BHP at 37°C for 24 h. CESP (100 lM). In our previous studies, we demonstrated that KGHDC is still inhibited after a 24-h treatment (Banerjee et al 2016). In addition, oxidant-induced cell death is evident after 24 h .…”
Section: Discussionmentioning
confidence: 89%
“…In our previous studies, we demonstrated that KGHDC is still inhibited after a 24‐h treatment (Banerjee et al . ). In addition, oxidant‐induced cell death is evident after 24 h (Shi et al .…”
Section: Resultsmentioning
confidence: 97%
“…Genetic association of the core metabolic enzyme DLD with late-onset AD [34]; and reduced activity of DLD-containing enzymes suggests glucose hypometabolism as a key factor in AD [36,38,444]. To determine how reduced glucose metabolism affects Aβ or tau toxicity in C.…”
Section: Chapter # Viii: General Discussionmentioning
confidence: 99%
“…Alzheimer's or Parkinson's disease [36][37][38][39][40]444]. Repressed activity of the KGDH complex, in particular by creating mice that are heterozygous for a knockout mutation of one of its subunits (E2), decreases glucose utilization in the cortex, which mimics the situation in cortical neurodegenerative diseases [41,42].…”
Section: Introductionmentioning
confidence: 99%